Generating novel focal patterns for radial variant vector beam focusing through a dielectric interface - Lavanya, Maruthasalam; Thiruarul, Duraisamy; Rajesh, Karuppaiya Balasundaram; Jaroszewicz, Zbigniew (Photonics Letters of Poland, 2023)
Electric and magnetic energy densities as well as energy flux (Poynting vector) for radial variant vector beam focusing through a dielectric interface is analyzed numerically based on vector diffraction theory. The electric and magnetic energy densities are tailored by properly manipulating the radial as well as initial phases to generates novel focal patterns in the focal area. These peculiar properties may find applications in fields such as optical trapping, optical recording, magnetic recording, and magnetic resonance microscopy and semiconductor inspection. Full Text: PDF References S.N. Khonina, I. Golub, "Optimization of focusing of linearly polarized light ", Opt. Lett. 36 352 (2011). CrossRef V.V. Kotlyar, S.S. Stafeev, Y. Liu, L. O'Faolain, A. A. Kovalev, "Analysis of the shape of a subwavelength focal spot for the linearly polarized light", Appl. Opt. 52 330 (2013). CrossRef S. Sen, M.A. Varshney, D. Varshney, "Relativistic Propagation of Linearly/Circularly Polarized Laser Radiation in Plasmas", ISRN Optics. 2013 1 (2013). CrossRef M. Martínez-Corral, R. Martínez-Cuenca, I. Escobar, G. Saavedra, "Reduction of focus size in tightly focused linearly polarized beams", Appl. Phys. Lett. 85 4319 (2004) . CrossRef J. Lekner, "Polarization of tightly focused laser beams", Opt. A: Pure Appl. Opt. 5, 6 (2003). CrossRef H. Guo, X. Weng, M. Jiang, Y. Zhao, G. Sui, Q. Hu, Y. Wang, S. Zhuang, "Tight focusing of a higher-order radially polarized beam transmitting through multi-zone binary phase pupil filters", Opt.Express 21, 5363 (2013). CrossRef C.-C. Sun, C.-K. Liu, "Ultrasmall focusing spot with a long depth of focus based on polarization and phase modulation", Opt. Lett. 28, 99 (2003). CrossRef G.H. Yuan, S.B. Wei, X.-C. Yuan, "Nondiffracting transversally polarized beam", Opt. Lett. 36, 3479 (2011). CrossRef P. Yu, S. Chen, J. Li, H. Cheng, Z. Li, W. Liu, B. Xie, Z. Liu, J. Tian, "Generation of vector beams with arbitrary spatial variation of phase and linear polarization using plasmonic metasurfaces", Opt. Lett. 40, 3229 (2015). CrossRef Z. Chen, T. Zeng, B. Qian, "Complete shaping of optical vector beams", J. Ding, Opt. Express 23, 17701 (2015). CrossRef Z. Liu, Y. Liu, Y. Ke, Y. Liu, W. Shu, H. Luo, S. Wen, "Generation of arbitrary vector vortex beams on hybrid-order Poincaré sphere", Photon. Res. 5, 15 (2017). CrossRef Z. Man, Z. Bai, S. Zhang, J. Li, X. Li, X. Ge, Y. Zhang, S. Fu, "Focusing properties of arbitrary optical fields combining spiral phase and cylindrically symmetric state of polarization", J. Opt. Soc. Am. A 35, 1014 (2018). CrossRef Z. Man, S. Fu, G. Wei, "Focus engineering based on analytical formulae for tightly focused polarized beams with arbitrary geometric configurations of linear polarization", J. Opt. Soc. Am. A 34, 1384 (2017). CrossRef Z. Man et al, "Optical cage generated by azimuthal- and radial-variant vector beams", Appl. Opt. 57 (2018). CrossRef S.S. Stafeev, V.V Kotlyar, A.G. Nalimov, E.S. Kozlova, "The Non-Vortex Inverse Propagation of Energy in a Tightly Focused High-Order Cylindrical Vector Beam", IEEE Photon. J., 11, 1 (2019). CrossRef S.S. Stafeev, V.V. Kotlyar, "Elongation of the area of energy backflow through the use of ring apertures", Opt. Commun.450 (2019) 67-71. CrossRef S.S. Stafeev, V.V. Kotlyar, A.G. Nalimov, "Energy backflow in in a tightly focused high-order cylindrical vector beam", Proc. SPIE 11025, 1102518 (2019). CrossRef N.G. Orji, M. Badaroglu, B.M. Barnes, "Metrology for the next generation of semiconductor devices", Nat. Electron. 1, 532 (2018). CrossRef P. Torok, P. Varga, G.R. Booker, "Electromagnetic diffraction of light focused through a planar interface between materials of mismatched refractive indices: structure of the electromagnetic field. I", I, J. Opt. Soc. Am. A 12, 2136 (1995). CrossRef P. Torok, P. Varga, Z. Laczik, G.R. Booker, "Electromagnetic diffraction of light focused through a planar interface between materials of mismatched refractive indices: an integral representation", J. Opt. Soc. Am. A., 12, 325 (1995). CrossRef Z. Zhou, L. Zhu, "Tight focusing of high order axially symmetric polarized beams through a dielectric interface", Optik, 124, 2219 (2013). CrossRef J. Shu, Z. Chen, J. Pu, Y. Liu "Tight focusing of a double-ring-shaped, azimuthally polarized beam through a dielectric interface", J. Opt. Soc. Am. A 31, 1180 (2014). CrossRef K. Hu, Z. Chen, J. Pu., "Generation of super-length optical needle by focusing hybridly polarized vector beams through a dielectric interface", Opt. Lett. 37, 3303 (2012). CrossRef B. Richards, E. Wolf, "Electromagnetic diffraction in optical systems, II. Structure of the image field in an aplanatic system", Proc. R. Soc. London A 253, 358 (1959). CrossRef